Learning English online: the questions of skill, will, self-regulation and academic performance / Kamisah Ariffin, Norizul Azida Darus and Norhajawati Abd Halim - Ariffin, Kamisah; Darus, Norizul Azida; Abd Halim, Norhajawati (Akademi Pengajian Bahasa, 2021)
The purpose of this study was to identify the relationships between ESL students’ strategic learning and their academic performance in the English course. This was measured using the adapted version of the Learning and Study Strategies Inventory (LASSI) that examines students’ strategy used in learning English under the dimensions of skill, will and self-regulation. Although research on this topic has been repleted, those that employ LASSI as the instrument of measurement in the English course are scarce. 150 students from various faculties in a local university took part in the study. Using self-reported LASSI questionnaire online, the results indicate a significant correlation between students’ strategic learning and their academic performance. Such findings imply that students need to have the skills in learning English, their willingness to learn and also their self-regulation in order to be successful in learning English online. Without all these elements, students will not be able to learn English